1998
DOI: 10.1093/carcin/19.5.747
|View full text |Cite
|
Sign up to set email alerts
|

Restored gap junctional communication in non-tumorigenic HeLa-normal human fibroblast hybrids

Abstract: Gap junctional intercellular communication (GJIC) has been implicated in homeostasis, development, differentiation, wound healing or regeneration and adaptive responses of differentiated cells. The dysfunction of homologous or heterologous GJIC has been associated with the tumorigenic phenotype. Restoration of growth control and the suppression of the tumorigenic phenotype have been previously associated with the up-regulation of GJIC by various anti-tumorigenic chemicals or transfection of connexin genes into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Their study found HepG2, HeLa and HEK-293T cells supporting reduced levels of cell-to-cell transmission. It is likely that the CMFDA diffusion in these cells is impaired as they, unlike Huh7, contain low numbers of gap junctions or none at all (Carruba et al , 2004; Clayton et al , 2005; de Feijter-Rupp et al , 1998; Stong et al , 2006). In our co-culture system, we found no evidence for passive diffusion of EGFP from recipient to donor cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Their study found HepG2, HeLa and HEK-293T cells supporting reduced levels of cell-to-cell transmission. It is likely that the CMFDA diffusion in these cells is impaired as they, unlike Huh7, contain low numbers of gap junctions or none at all (Carruba et al , 2004; Clayton et al , 2005; de Feijter-Rupp et al , 1998; Stong et al , 2006). In our co-culture system, we found no evidence for passive diffusion of EGFP from recipient to donor cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The role of GJIC in the neoplastic transformation of these hybrid cells has not been studied in detail. There is evidence for loss of homologous coupling in a spontaneously arising tumorigenic segregant and this was associated with loss of expression of connexin43 at the mRNA and protein levels (36). In the present study we have examined the status of homologous and heterologous GJIC in a UVC-induced tumorigenic HeLaϫskin fibroblast cell line, as well as its revertants with less aggressive tumorigenic phenotypes.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, normal cells, exposed to tumor promoting agents, and malignant tumor cells are frequently characterized by reversible‐ or stable‐disrupted GJIC, respectively [1,2]. Thus, the disruption of GJIC has been hypothesized to overcome the suppression of initiated cells by the surrounding normal cells and to allow the clonal expansion of preneoplastic cells, leading to an idea that the Cx genes belong to a family of tumor suppressor genes [12–15]. Combined with these observations, we expect that the transforming RNA3S + would also suppress the translation of gap junction proteins which would lead to the inhibition of GJIC.…”
Section: Introductionmentioning
confidence: 98%